Exploring Technical Debt on IoT Software Projects - Rios, Nicolli; Spínola, Rodrigo; Travassos, Guilherme (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
It is common for software projects to incur technical debt (TD) during their development process. It should be no different for IoT software projects, mainly characterized by integrating devices and communication technologies. This work reduces a gap in the technical literature by presenting an investigation of TD in the context of IoT software projects. To this end, it describes how TD has been perceived, identified, and represented when developing two IoT software projects regarding monitoring an individual’s oxygenation level (OximetroIoT) and biosafety indicators in classrooms and laboratories (SAFE-UFRJ). By applying a TD management strategy, we identify, monitor, and pay TD items incurred during the development process of those projects. It allowed us to identify 153 TD items grouped into 16 different TD types (three new ones compared with current taxonomies) and 75 effects due to their presence. Overall, the investigated IoT software projects experience TD differently from software projects.